Girl Child Education and Its Socio-Cultural View in Our Society - Abiodun Eunice Olatide (Britain International for Academic Research (BIAR-Publisher), 2023)
The study examined the importance of girl child education and its significance to our society and entire nation in general. The paper also reviewed literature on the cultural, economic, social and traditional aspect of people’s life, particularly on girl child in our society and its benefits to training a girl child and to provide for their needs. Girl child education in some countries of Africa and some culture in Nigeria were also considered. The study examined girl child education among the secondary school students of four selected local government areas and 5Five schools where 20students that make up 400 students was used as sample for the study in Kwara State. Two research questions were raised while two hypotheses were formulated. Descriptive survey design was adopted for the study. The findings revealed some cultural, traditional beliefs and practice of the people have constituted the major challenges to girl child education.